Alkylation of isobutane/butene promoted by fluoride-containing ionic liquids. (1st January 2018) - Zhang, Honghua; Liu, Ruixia; Yang, Zhiqiang; Huo, Feng; Zhang, Ruirui; Li, Zihang; Zhang, Suojiang; Wang, Yanji
Graphical abstract: Highlights: Fluoride-containing ILs were employed as additives and their promoting performance was investigated in H2 SO4 alkylation process. New species of HF, [PF6−x−2y (HSO4 )x (SO4 )y ] − and [SbF6−x−2y (HSO4 )x (SO4 )y ] − were formed through acidolysis of [Bmim][PF6 ] or [Bmim][SbF6 ] in H2 SO4 . The possible promoting mechanism of fluoride–containing ILs was proposed. Abstract: In this work, the alkylation of isobutane and butene, catalyzed by sulfuric acid in the presence of the fluoride–containing ionic liquids [Bmim][PF6 ] and [Bmim][SbF6 ], was investigated. The use of the binary mixture catalysts brought to a higher C8 selectivity and longer catalyst lifetime, compared with the results obtained when working with sulfuric acid only. This was attributed to the formation of new species when [Bmim][PF6 ] or [Bmim][SbF6 ] are added to sulfuric acid. The acidolysis of [Bmim][PF6 ] and [Bmim][SbF6 ] was accompanied by the release of hydrogen fluoride (HF) and the decomposition of anions to [PF6−x−2y (HSO4 )x (SO4 )y ] − and [SbF6−x−2y (HSO4 )x (SO4 )y ] −, respectively. The presence of these new species after acidolysis was measured and confirmed by ion chromatography, 1 H–Nuclear Magnetic Resonance (NMR), 19 F–NMR and 31 P–NMR. The production of HF and the complexation of anions and carbenium ions both play an important role in stabilizing the carbenium ion and improving the catalytic performance.